Importance and fitness of family medicine milestone project from America to Taiwan - Shih-Ming Li; Yaw-Wen Chang; Ming-Nan Lin; Chi-Wei Lin; Chyi-Her Lin; Cheng-Chieh Li; Ming-Hwai Lin; Yin-Fan Chang; Zih-Jie Sun; Fang-Yih Liaw; Jaw-Shiun Tsai; Shinn-Jang Hwang; et al. (BMC Medical Education)
Abstract Background The six core competencies of ACGME - patient care (PC), medical knowledge (MK), systems-based practice (SBP), practice-based learning and improvement (PBLI), professionalism (PROF), and interpersonal and communication skills (ICS) - represent domains in which physicians must ultimately demonstrate competence. Although the ACGME’s six core competencies have been applied in Taiwan with the milestone project, the application of the six core competences in the Family Medicine milestones for residency training have not yet been established. Methods We recruited 61 family medicine physicians from 25 hospitals from four major geographic areas for a Delphi round one survey and 72 physicians from 27 hospitals for a Delphi round two survey. With 5-point scales, the Cronbach’s alphas for both importance and fitness were 0.98 in round one. In round two, the Cronbach’s alphas were 0.86 and 0.83 for importance and fitness. The mode and quartile deviation in Delphi method, importance-performance analysis (IPA), and importance-performance matrix analysis (IPMA) were used for three stages IPA process. Results In IPA, a total of 72.7% (16/22) of the sub-competencies exhibited high importance and fitness, with a mean score ≥ 4.7; the exceptions were PC-1 (cares for acutely ill or injured patients), MK-2 (critical thinking skills in patient care), SBP-1 (cost-conscious medical care), PBLI-3 (improves systems), PROF-3 (humanism/cultural proficiency), and ICS-4 (utilizes technology). In IPMA, the performance value of six core competencies for FMM-Taiwan was 92.6 when considering the importance and fitness indices of the 22 sub-competencies. Conclusions The accordance of the ACGME’s milestones to Taiwan was acceptable to good and related milestones could been developed for residency training.